2017
DOI: 10.1038/ejhg.2017.147
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Glaucoma spectrum and age-related prevalence of individuals with FOXC1 and PITX2 variants

Abstract: Variation in FOXC1 and PITX2 is associated with Axenfeld-Rieger syndrome, characterised by structural defects of the anterior chamber of the eye and a range of systemic features. Approximately half of all affected individuals will develop glaucoma, but the age at diagnosis and the phenotypic spectrum have not been well defined. As phenotypic heterogeneity is common, we aimed to delineate the age-related penetrance and the full phenotypic spectrum of glaucoma in FOXC1 or PITX2 carriers recruited through a natio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…Within the limits of available patient data (four known CPAMD8 cases with glaucoma, plus four without glaucoma), we estimate glaucoma penetrance in CPAMD8 -related ASD to be ~50% (4/8), which is similar to more reliable estimates in ARS 17,18 .…”
Section: Foxc1 (Siggs Et Al Unpublished) Other Asds Notably Ars Csupporting
confidence: 59%
See 1 more Smart Citation
“…Within the limits of available patient data (four known CPAMD8 cases with glaucoma, plus four without glaucoma), we estimate glaucoma penetrance in CPAMD8 -related ASD to be ~50% (4/8), which is similar to more reliable estimates in ARS 17,18 .…”
Section: Foxc1 (Siggs Et Al Unpublished) Other Asds Notably Ars Csupporting
confidence: 59%
“…The most common ASD presentation is Axenfeld-Rieger anomaly, known as Axenfeld-Rieger syndrome (ARS) when associated with systemic features. Individuals with ARS have a 50-60% lifetime risk of developing glaucoma, which can occur as early as the first year of life (Shields 1983;Souzeau 2017). …”
mentioning
confidence: 99%
“…Patients may develop into glaucoma at a very young age, or they may be asymptomatic for a long time from childhood to youth until high intraocular pressure occurs. It is reported that more than 50% patients with FOXC1 -related ARS will develop into glaucoma eventually and the median onset age of glaucoma diagnosis is 6 ± 13.0 years [ 3 , 24 , 25 ]. In this study, although the 5-year-old boy had normal intraocular pressure and there were no alterations of the optic nerve, he is still at high risk of developing glaucoma.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 50% of ARS patients will develop into glaucoma, with an age of onset ranging from birth to late in adulthood [ 1 , 2 ]. Onset of glaucoma typically occurs before the teenage years [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, polymorphism studies of the PITX2 gene were carried out on humans and mainly focused on its associations with diseases [22][23][24]. In livestock, polymorphisms of the PITX2 gene have been reported to be related to the milk traits of dairy goats and the meat quality and growth of pigs [25][26][27].…”
Section: Introductionmentioning
confidence: 99%